Testing biodegradable mesh compositions to improve coral microfragmentation outcomes - Rivera, Andreina (2026)
Introduction: Coral microfragmentation is a widely used technique in reef restoration, both in situ and in land-based nurseries. Typically, microfragments are individually attached to pedestals or artificial substrates, which requires substantial time and labor investment in the nursery and during field outplanting. An alternative approach involves the use of biodegradable meshes fixed to the substrate as a single unit supporting multiple microfragments. However, the optimal material combinations that provide the mechanical strength, stability, and adhesion necessary to maintain fragments in place after partial material degradation remain unknown. Therefore, experimental evaluation of biodegradable materials that optimize both stability and coral growth is a priority. Objective: To evaluate whether two polymers (PCL and CAPA) combined with different concentrations of CaCO₃ influence coral growth rates and operational efficiency in both nursery and field conditions. Methods: A controlled multifactorial experiment using a fully randomized block design was conducted over six months. The effect of mesh composition on cumulative growth in area and volume of Montastraea cavernosa was assessed using photogrammetry (Structure from Motion, SfM). Additionally, operational times in the nursery (handling, attachment, and cleaning) and during field outplanting were compared with and without mesh use. Results: No statistically significant effects of mesh composition on growth rates were detected during the study period. Mean a real growth ranged from 0.5 to 0.8 mm², with a significant interaction among treatment, tank, and time, indicating low growth and high variability among tanks. Volumetric increase ranged from 0.25 to 0.62 cm³, with no significant differences among treatments. However, mesh uses reduced nursery handling time by approximately 20 minutes per rack of 18 fragments. Conclusions: Regardless of composition, biodegradable meshes represent a viable alternative to optimize asexual propagation through microfragmentation, improving operational efficiency without compromising coral growth.